Objek Wisata Pemandian Air Panas (Wair Gahu) Blidit Sebagai Daya Tarik Wisata Alam - Yosef Dentis; Florida Oa Min (Ekspektasi: Jurnal Pendidikan Ekonomi, 2021)
The aims of this study are: 1) To find out the early history of the emergence of Blidit hot springs. 2) To find out the condition of tourist facilities in the Blidit hot spring tourist attraction. 3) To find out the public's view on the potential utilization of the Blidit hot spring tourist attraction. This study uses a qualitative descriptive method. The results showed that: the early history of the emergence of Blidit hot springs was first found by the Blidit people who wanted to go hunting in the forest and one of them stepped on the water and felt the water was hot but they thought the water came from Mount Egon because Mount Egon is a mountain fiery. The water emerged from the ground through cracked soil and it is said that at that time there was a person named gahu which means heat was cut and his body was stored in the water and at that time also in the bathing place there was a guard and when he wanted to visit that place he had to many people and keep things in that place such as roko, money and betel nut when in that place, visitors should not utter harsh words. The condition of tourist facilities for tourist attractions, Blidit hot spring baths, is classified as not good. Judging from the condition or state of the hot springs, there are still very few facilities and are not cared for and kept clean where visitors still use private vehicles and access roads that still use paths that are still in the form of soil and rocks.